Investigating factors affecting work engagement among employee in the oil and gas companies in Malaysia / Muhammad Fahimi Hasrat Nazarudin - Hasrat Nazarudin, Muhammad Fahimi (Faculty of Business and Management, 2019)
Malaysia is among the highest proportions of employees in the world that are not engaged with their work are from Malaysia. Based on the similar study, the percentage of employees in Malaysia that have engagement with their work is only at 11 per cent, while 81 per cent is not engaged and eight per cent is actively disengage (New Straits Times, 2016). This study investigates factors affecting work engagement among employee in the oil and gas companies in Malaysia. This study used “Utrecht work engagement scale” survey research to collect data from sample (N=397) of employee working in oil and gas companies in Malaysia. This study used four factors or independent variables which is social interaction at work, psychological availability, psychological meaningfulness, and psychological safety and work engagement as dependent variable. The findings from this study shows that work engagement has significant relationship with other variables. This study concluded that social interaction at work is the most significant factor that contribute toward the work engagement among employee in oil and gas companies in Malaysia.